Tough, flexible, and durable all-polyampholyte hydrogel supercapacitor - Xuefeng Li; Yonglin Wang; Dapeng Li; Caiwei Shen; Mengfan Chen; Shijun Long; Yiwan Huang (Polymer Testing, 2022)
Most of the currently developed flexible energy storage devices lack sufficient flexibility to withstand various deformations, such as stretching, compression, and bending under the action of external forces. It also lacks sufficient and stable energy output. In this work, we use the flexible material hydrogel as electrode and electrolyte to design an all-hydrogel integrated flexible supercapacitor. Both the electrode and the electrolyte contain the same polyampholyte hydrogel P(NaSS-co-DMAEA-Q) matrix, making them possess superb self-adhesion due to the electrostatic interaction between the anion and cation group, and highly softness/toughness thanks to the energy-dissipative mechanism. The electrode of supercapacitor is a composite of activated carbon and hydrogel, which has excellent mechanical and electrical properties. Supercapacitors prepared from hydrogel electrodes and hydrogel electrolytes are inherently scalable/compressible, and simultaneously deliver high areal capacitance (128.9 mF cm−2 at 1 mV s−1 and 340.18 mF cm−2 at 0.1 mA cm−2) and maintain stable energy output. The combination of simple device structure, stable mechanical properties and excellent electrical properties makes flexible supercapacitors promising for applications in wearable electronics/devices and energy storage.